Community Participation of Mangrove Forest Preservation in Batang Gasang Padang Pariaman District - Susi Erienti; Indang Dewata (Pascasarjana, Universitas Negeri Padang, 2019)
The purpose of this study is to study community participation in the preservation of mangrove forests located in Nagari GasanGadang and Nagari Malai V, BatangGasang Sub-District, Padang Pariaman Regency, West Sumatra Province. The indicators consist of (1) Description of Community Aspects, Measured parameters of community participation that are linked to 3 socioeconomic status, namely Level of Education, Employment and Income; (2) Description of Biological Aspects, Parameters measured by the level of density of mangroves by making Measuring Plots measuring 20 x 20 m totaling 10 Measuring Plots that are spread evenly. Primary data obtained directly in the field and interviews with 65 respondents while secondary data is supporting data obtained from relevant agencies. The data analysis technique used is the analysis of community participation and the analysis of mangrove species density using the Mann-Whitney Test statistical analysis for testing the difference in species density and the Kruskal-Wallis Test statistical analysis for testing the level of community participation with the SPSS 15 Program. The results showed that the results of the hypothesis test of differences in density revealed that the Z value for density was -2,243 (p <0.05), meaning that the density of mangrove forests showed an average difference, that there were significant differences in the level of density of mangrove forests. While the Difference Test Results of Community Participation with Chi-Square based on education amounted to 0.513 (p> 0.05), meaning that community participation on the preservation of mangrove forests at the educational level did not show any difference, while based on the Chi-Square value of 16,203 (p <0 , 05), means that there are significant differences in community participation between work. for Chi-Square income of 0.248 (p> 0.05), there was no significant difference in community participation between income levels. Based on the socio-economic aspect, that community participation whose income <1 million is very low, people's income 1 - 1.5 million participation is low while the community's income> 1.5 million participation is high in maintaining the preservation of mangrove forests in BatangGasang District.